TRANSPARANSI DAN AKUNTABILITAS DALAM LAPORAN KEUANGAN PEMERINTAH KOTA GORONTALO 2021-2023 - Fauziah Husain; Hisantiawati Guhung; Nurlian Jerita; Nur Hikmah Dai; Ziamudin Gustia Rahim (Jurnal Riset Akuntansi, 2025)
This study examines the implementation of transparency and accountability in the financial statements of the Gorontalo City Government during the 2021-2023 period. This study is important considering the strategic role of transparency and accountability in realizing good governance and increasing public trust in state financial management. This study uses a qualitative descriptive approach by conducting an exploratory study of literature and data collection techniques using literature studies. Secondary data was obtained from previous research journals through Google Scholar. The results of the analysis show that the Gorontalo City Government's financial statements show a positive trend in terms of transparency and accountability. Regional financial independence has increased, with the ratio of PAD to total revenue reaching 23.66% (2021), 27.58% (2022), and 26.87% (2023). There has been a shift in spending priorities from operating expenditure to capital expenditure, indicating a focus on infrastructure development and fixed assets. The study highlights several factors that affect transparency and accountability, such as political engagement, legal and regulatory frameworks, and the quality of resources. Increased transparency and accountability requires comprehensive measures, including increased public involvement in the budgeting and oversight process, as well as strengthening the legal and regulatory framework governing regional financial management.